Feeding and Manual Brushing Influence the Release of Oxytocin, ACTH and Cortisol Differently During Milking in Dairy Cows - Wredle, Ewa; Svennersten-Sjaunja, Kerstin; Munksgaard, Lene; Herskin, Mette S.; Bruckmaier, Rupert M.; Uvnäs-Moberg, Kerstin (Frontiers in Neuroscience, 2022)
Aim This study aimed to examine the effects of feeding or abdominal brushing on the release of the hormones oxytocin, ACTH and cortisol and on milk production, during milking in dairy cows Methods Twelve cows in early lactation were used (2×2 factorial experimental design), testing the effects of two types of sensory stimulation during milking over a three day period; feeding concentrate or manual abdominal brushing (1 stroke/sec). Blood samples for hormone analyses were collected at time at -15, -1, 0 (onset of cluster), every min for 8 min, at 10, 12, 14, 16, 30 and 60 min. Hormone levels were assayed and AUC was calculated. Milk samples were analysed for fat, protein and lactose content. Milk yield, flow and milking time were recorded. Results Milking was associated with an immediate and significant rise of oxytocin. When milking was combined with feeding, significantly higher levels of oxytocin were observed at 2 and 4 minutes (p<0.05). No effect of brushing on oxytocin levels was observed. Milking alone was associated with a significant rise of ACTH levels. Feeding in connection with milking reduced the immediate rise of ACTH levels (p<0.05) and AUC (p<0.02), whereas no effects of brushing were found. Milking caused a progressive rise of cortisol levels. Concomitant feeding did not influence cortisol levels, whereas brushing significantly decreased cortisol levels at 1, 5 and 14 minutes after onset of milking (p<0.05). Milk yield and duration of milking increased significantly, when milking was associated with feeding (p<0.01 and p<0.05). No influence of manual abdominal brushing were found. Conclusion Feeding during milking increases oxytocin release and decreases ACTH levels. Abdominal brushing did not influence these variables, but decreased cortisol levels. These data demonstrate that activation of afferent vagal nerves and of cutaneous sensory nerves from the abdominal afferents influence milking related hormone release differently.